STRATEGY FOR IMPLEMENTING EMBEDDED SYSTEMS PROGRAMMING LEARNING WITH THE STUDENT CENTERED LEARNING METHODS - Ramandhani, Sahid; Yusuf, Arya; Murdiyani, Kenanga Kusuma; Wulida, Siti Nursipa (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
Student centered learning (SCL) focuses on students achieving learning objectives. This study aims to determine the impact of applying student centered learning (SCL) learning methods in embedded system programming subjects. The student centered learning (SCL) method is used to train creativity and improve student understanding in carrying out practical learning in the classroom. The subjects of this study were 64 students of class XI Electronics Engineering from 2 classes, namely TE 1 and TE 2. This research used descriptive qualitative research methods. The data analysis used is descriptive statistics. In each meeting, students can fulfill the expected learning concepts and fulfill part of the learning outcomes so that the learning objectives and practicum results can be achieved well. The results showed that the application of the student centered learning (SCL) model can improve student learning outcomes by 4,12%, obtained from learning results with an average job sheet work value of 83.71 in the TE 1 class and 84.28 in the TE 2 class. This shows that through the student centered learning (SCL) approach students can understand and practice the learning material well. The application of learning with the student centered learning (SCL) model received a positive response from students because students felt freer in learning and practicing embedded system programming material.